Religion on an Ordinary Day in Canada: Religion and Sexuality in Mainstream and Alternative Media - Shipley, Heather (Journal of religion, media and digital culture, 2021)
Abstract This article examines media portrayals of the relationship between (non)religion and sexuality in both mainstream and lgbt media in Ottawa, Ontario, Canada. The goal of examining mainstream and lgbt media is to consider how religion and sexuality are represented within differing media sources, whether there are variations in representation across these sources and to consider what an ‘ordinary day’ might look when it comes to these identity categories in non-mainstream media sources.